Analisis Laporan Keuangan Dalam Mengukur Kinerja Keuangan Pada PT. Perkebunan Nusantara VI (PTPN VI) Periode 2015-2019 - Nur Sangkut; Putri Handayani; Fenni Juniati Manurung; Ratih Kusumastuti (Universitas 45 Surabaya, 2023)
The purpose of this study is to determine the financial performance of PT. Nusantara Plantation VI (PTPN VI). Analysis of PTPN VI's financial ratios from 2015 to 2019. Current Ratio, Quick Ratio, Cash Ratio, Debt To Assets Ratio, Debt To Equity Ratio, Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM), and Gross Profit Margin (GPM) are all components of financial ratio analysis. The data used in this study is PTPN VI's financial report data from 2015 to 2019. The data analysis method used is the horizontal analysis method, which compares financial reports for several timeframes. Based on data analysis it can be seen that PTPN VI's liquidity ratio, solvency ratio, and profitability ratio indicate that PTPN VI's financial performance is not good or not good and or unsatisfactory in the five years of research.